Setting Up and Implementation of the Parallel Computing Cluster in Higher Education - Serik, Meruert; Karelkhan, Nursaule; Kultan, Jaroslav; Zulpykhar, Zhandos (International journal of emerging technologies in learning, 2019)
In this article, we describe in detail the setting up and implementation of the parallel computing cluster for education in the Matlab environment and how we solved the problems arising on this way. We also describe the comparative analysis of parallel computing cluster by the example of matrix multiplication by a vector with large dimensions. First calculations were performed on one computer, and then on a parallel computing cluster. In the experiment, we proved the effectiveness of parallel computing and the necessity of the setting up of the parallel computing cluster. We hope that the creation of a parallel computing cluster for education will help in teaching the subject of parallel computing at higher schools that do not have sufficient hardware resources. This paper presents unique setting up and implementation of the parallel computing cluster for teaching and learning of the parallel computing course and a wide variety of information sources from which instructors can choose.